2021
DOI: 10.1016/j.ijid.2021.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of Xpert MTB/RIF on contrast-enhanced ultrasound-guided pleural biopsy specimens for pleural tuberculosis

Abstract: Background: A 3-year prospective study was conducted to evaluate the efficacy of Xpert MTB/RIF (Xpert) in the diagnosis of pleural tuberculosis (pTB) on contrast -enhanced ultrasound (CEUS)-guided pleural biopsy specimens. Method: Patients suspected with pTB were prospectively enrolled to receive CEUS-guided biopsy. Specimens (pleural tissue and fluid) were submitted for Xpert and other routine examinations. Surgical thoracoscopy was performed on undiagnosed cases. Result: A total of 316 patients were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Previous study included 58 patients with pleural-based peripheral pulmonary lesions to evaluate the diagnostic value of CEUS guided biopsy and obtained an overall diagnostic rate of 98.3% [ 9 ]. Our previous studies also found the diagnostic efficiency of CEUS guided biopsy in superficial lymph nodes and pleural tuberculosis [ 10 , 11 ]. Furthermore, we conducted a 3-year prospective clinical study to evaluate the value-added effect of CEUS-guided pleural biopsy in the diagnosis of pleural based lesions determined by imaging.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Previous study included 58 patients with pleural-based peripheral pulmonary lesions to evaluate the diagnostic value of CEUS guided biopsy and obtained an overall diagnostic rate of 98.3% [ 9 ]. Our previous studies also found the diagnostic efficiency of CEUS guided biopsy in superficial lymph nodes and pleural tuberculosis [ 10 , 11 ]. Furthermore, we conducted a 3-year prospective clinical study to evaluate the value-added effect of CEUS-guided pleural biopsy in the diagnosis of pleural based lesions determined by imaging.…”
Section: Introductionmentioning
confidence: 59%
“…However, the majority of CEUS diagnostic studies are focused on malignant tumors. Our recent study showed that CEUS-guided biopsy could increase the pathogenetic detection rate of pleural TB by accurately identifying necrosis [ 11 ]. In the present study, 100% infectious pleural lesions were diagnosed by CEUS guided biopsy and 71.88% obtained the microbiological evidence.…”
Section: Discussionmentioning
confidence: 99%
“…We found 1095 citations through a search of electronic databases and located another two from additional sources ( Fig 1 ). In all we assessed 146 full-text publications in detail against our inclusion criteria, and finally included 74 for our analysis [ 23 96 ]. Of these, 64 (86.5%) studies evaluated Xpert alone, five (6.8%) evaluated Ultra alone, and five (6.8%) evaluated both tests concurrently ( S1 Table of online supplement).…”
Section: Resultsmentioning
confidence: 99%
“…One (1.4%) study was conducted exclusively in HIV seropositive patients [ 43 ], while seven (9.5%) others included a variable number of such subjects [ 37 , 38 , 42 , 44 , 53 , 70 , 89 ]. There were no HIV seropositive patients in thirteen (17.6%) publications [ 30 , 47 , 63 , 73 , 74 , 76 , 78 , 79 , 83 , 84 , 88 , 92 , 96 ], while the remaining did not provide any information. Ten investigators thawed cryopreserved fluid samples for their tests [ 23 , 31 , 35 , 42 , 60 , 66 , 73 , 78 , 80 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound-assisted Abrams' needle biopsy still seems to be the better choice in allowing the diagnosis of pleural tuberculosis compared to ultrasound-guided Tru-Cut needle biopsy (65-67). Sun et al (68) showed that the Xpert MTB/RIF assay may increase the diagnostic sensitivity for TB in histological pleura samples obtained through contrast enhanced ultrasound (CEUS) guided biopsy. CEUS, on turn, demonstrated to be an efficient, minimally invasive, and safe method for guide biopsy.…”
Section: Pleural Effusionmentioning
confidence: 99%